Consumers, society and marketing: A sustainability perspective - Mutum, Dilip S.; Ghazali, Ezlika M. (Switzerland Springer, 2023)
Environment and social responsibility are paramount for any modern business strategy, and the field of marketing is adapting itself to the new focus on sustainability. The study of the interface between consumers, society, and marketing is crucial for understanding the complex interactions between individuals and the products and services they consume and the resulting implications.